PENGEMBANGAN TEKNOLOGI PEMASARAN PRODUK UMKM MELALUI DIGITAL MRSE BAGI PELAKU USAHA DI DESA KETAPANG KABUPATEN BANDUNG - Yuliyantini, Yuliyantini; Kartika, Tuti; Marbun, Jumayar (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2022)
Small business actors are required to be able to innovate in following the development of digital-based product marketing systems for business sustainability and welfare. MRSE (Management of Reseller and Event) digital marketing technology is the result of engineering from digital and conventional marketing technology designed to improve skills and sales results for small business products for poor families who experience gaps in using digital technology. This study aims to obtain the final design of the MRSE digital marketing technology. This study uses a qualitative approach with the Participatory Action Research (PAR) method. This research was applied to two groups of small business actors of glutinous rice and knitting bags in Katapang Village, Katapang District, Bandung Regency. The results of this study found that the initial conditions for marketing MSME products were carried out conventionally by entrusting the product to local stalls and traditional markets. The planning for the implementation of MRS digital marketing technology includes digital marketing media, marketing partners, and breadth of targets. The results of the study found the final design of MRSE digital marketing technology engineering which was refined into 4 (four elements) namely 1) the use of digital marketing media with a market place and social media (village website, whatsapp business, shopee, and facebook), 2) marketing partners involving resellers namely local village youth, 3) the breadth of sales targets carried out to the national level, and 4) marketing by using events.